2022
DOI: 10.1096/fj.202200468rr
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a fragile X messenger ribonucleoprotein 1 (FMR1) mRNA gain‐of‐function toxicity mechanism contributing to the pathogenesis of fragile X‐associated premature ovarian insufficiency

Abstract: Fragile X‐associated premature ovarian insufficiency (FXPOI) is among a family of disorders caused by expansion of a CGG trinucleotide repeat sequence located in the 5′ untranslated region (UTR) of the fragile X messenger ribonucleoprotein 1 (FMR1) gene on the X chromosome. Women with FXPOI have a depleted ovarian follicle population, resulting in amenorrhea, hypoestrogenism, and loss of fertility before the age of 40. FXPOI is caused by expansions of the CGG sequence to lengths between 55 and 200 repeats, kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
(186 reference statements)
0
3
0
Order By: Relevance
“…The pathophysiology of FXTAS involves multiple mechanisms, including RNA toxicity [ 24 , 25 , 26 ], clogging of the proteasome [ 27 ], RAN translation [ 28 , 29 ], and mitochondrial dysfunction [ 30 , 31 , 32 ] (for more details, see Section 2 , ‘The molecular basis of FXPAC’). Recent papers have shown that males progress more rapidly in motor symptoms than females, presumably because of the protective effects in addition to the presence of the normal second X chromosome [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of FXTAS involves multiple mechanisms, including RNA toxicity [ 24 , 25 , 26 ], clogging of the proteasome [ 27 ], RAN translation [ 28 , 29 ], and mitochondrial dysfunction [ 30 , 31 , 32 ] (for more details, see Section 2 , ‘The molecular basis of FXPAC’). Recent papers have shown that males progress more rapidly in motor symptoms than females, presumably because of the protective effects in addition to the presence of the normal second X chromosome [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RNA-tagging approach allowed us to identify over a hundred and fifty proteins—including factors with translation regulatory properties. Some identified proteins overlapped with ones already described as binding to mutant FMR1 mRNA such as SRPK1 or TAR DNA-binding protein 43 (TDP-43) (Malik et al , 2021b; Rosario et al , 2022; Sellier et al , 2010; Jin et al , 2007; Cid-Samper et al , 2018; Sellier et al , 2017). Further, we described three new modifiers of RAN translation of this mRNA.…”
Section: Discussionmentioning
confidence: 94%
“…It is necessary for oocyte growth and follicle development, and its depletion causes changes in transcription and chromatin configuration, leading to premature ovarian failure (Liu et al, 2018). Our discovery that RPS26 regulates the level of FMRpolyG in cellular models sheds new light on the potential role of RPS26-related RAN translation in FXPOI, where FMRpolyG aggregates are detected in ovarian cells and contribute to the development and progression of fertility issues (Buijsen et al, 2016;Shelly et al, 2021;Rosario et al, 2022).…”
Section: Discussionmentioning
confidence: 98%